An atlas of the Ethiopian rural economy: expanding the range of available information for development planning - Chamberlin, Jordan; Tadesse, Mulugeta; Benson, Todd; Zakaria, Samia (SAGE Publications, 2007)
This article describes a recently released Atlas of the Ethiopian Rural Economy that synthesizes spatial information on agriculture and other aspects of the rural environment in Ethiopia from a number of secondary sources. A primary goal of the project was to increase the relevance and accessibility of this information for policy-makers and development program planners through its compilation and harmonization within a cartographic format. Understanding the many dimensions of a nation's rural economy is critical to policy-makers and program planners as they develop strategies to transform the rural economy in order to sustainably reduce rural poverty and accelerate broad economic growth. In many countries, there is a wealth of valuable and spatially explicit information that could enlarge and deepen such an understanding. However, this is often difficult to use because it is fragmented, found in many different formats, presented at different levels of aggregation, and held by agencies with different access policies and procedures. Several aspects of a statistical atlas of this nature recommend it as a model for initiating transformations in poor-access and fragmented information environments that characterize many developing countries. This article describes these characteristics, as well as the challenges that face those implementing such projects, and seeks to relate information projects of this nature to the broader importance of information access for guiding rural development policy and strategy formulation.